2017
DOI: 10.1128/jvi.00924-17
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-Mouth Disease (FMD) Virus 3C Protease Mutant L127P: Implications for FMD Vaccine Development

Abstract: The foot-and-mouth disease virus (FMDV) afflicts livestock in more than 80 countries, limiting food production and global trade. Production of foot-and-mouth disease (FMD) vaccines requires cytosolic expression of the FMDV 3C protease to cleave the P1 polyprotein into mature capsid proteins, but the FMDV 3C protease is toxic to host cells. To identify less-toxic isoforms of the FMDV 3C protease, we screened 3C mutants for increased transgene output in comparison to wild-type 3C using a Gaussia luciferase repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Presumably, a host protease is responsible for the 3CD cleavage seen, which occurs at a sequence close to the natural cleavage site. It would be interesting to fully ablate this cleavage event in Pichia or introduce mutations into 3C pro to reduce toxicity, as shown previously for foot-and-mouth disease virus, and determine the impact of these modifications on VLP production (44). We demonstrated that all three expression cassettes led to the correct processing of P1 through the detection of VP-1 using monoclonal antibody (MAb) 8650.…”
Section: Discussionmentioning
confidence: 58%
“…Presumably, a host protease is responsible for the 3CD cleavage seen, which occurs at a sequence close to the natural cleavage site. It would be interesting to fully ablate this cleavage event in Pichia or introduce mutations into 3C pro to reduce toxicity, as shown previously for foot-and-mouth disease virus, and determine the impact of these modifications on VLP production (44). We demonstrated that all three expression cassettes led to the correct processing of P1 through the detection of VP-1 using monoclonal antibody (MAb) 8650.…”
Section: Discussionmentioning
confidence: 58%
“…This result shows that the structural proteins are able to determine the antigenic specificity [3]. Studies have shown that the availability of free polypeptide chains in zone A and the tap-folding barrels of zone B and aspartic acid residue R56 in surface protein of VP3 could determine the binding with polyclonal antibodies [31]. Similarly, VP3 protein is crucial in recognizing the cellular heparin sulfate (HS) co-receptor of FMDV [32].…”
Section: Discussionmentioning
confidence: 97%
“…FMDV capsid precursor P1 is the precursor protein of VP1. P1 is finally processed into mature VP0, VP1, and VP3 proteins under the action of FMDV 3C protease (3C pro ) (32,33). In order to clarify whether the degradation of TPL2 is caused by the specificity of the VP1 protein in the P1 precursor, the effect of P1 on the expression level of TPL2 was first detected by Western blotting.…”
Section: Fmdv Vp1 Protein Promotes K48-linked Polyubiquitination Of Tpl2 and Degrades Tpl2 By The Proteasome Pathwaymentioning
confidence: 99%